2011
DOI: 10.2118/124719-pa
|View full text |Cite
|
Sign up to set email alerts
|

How To Prevent Loss of Zonal Isolation Through a Comprehensive Analysis of Microannulus Formation

Abstract: Summary Microannuli at the well cement-sheath interfaces may result in loss of zonal isolation, which is the source of many problems, such as sustainable annular pressures, crossflows between reservoirs, and undesirable flow behind the casing. The microannuli are commonly explained by variations in cement volume during hydration (chemical shrinkage/expansion) or by contraction of the casing because of a decrease in mud density/temperature because these could create a gap if the cement is unable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…Poor primary cement can occur by the development of fluid channels, casings that are not centered in the well, poor bonding and shrinkage, and losses of cement into the surrounding rock (68). Well operations can also damage cement through temperature and pressure changes (52,69).…”
Section: Mechanisms Of Wellbore-integrity Failurementioning
confidence: 99%
“…Poor primary cement can occur by the development of fluid channels, casings that are not centered in the well, poor bonding and shrinkage, and losses of cement into the surrounding rock (68). Well operations can also damage cement through temperature and pressure changes (52,69).…”
Section: Mechanisms Of Wellbore-integrity Failurementioning
confidence: 99%
“…Accounting for microannuli in a risk assessment is a challenge: They can appear when pressure (or temperature) in the well drops or formation pressure is increased, so cement-evaluation logs should, in theory, be repeated after every change in well use to confirm their existence, an expensive and logistically problematic option. Alternatively, one can use advanced thermomechanical models of cement-sheath behavior to predict the presence of microannuli (Bois et al 2011(Bois et al , 2012. Within the context of a basin-scale risk assessment, with its time and information constraints, however, there are substantial benefits in adopting a simplified model based on that in Lecampion et al (2013).…”
Section: Resultsmentioning
confidence: 99%
“…As described in the previous section, cement sheaths typically fail because of volumetric instability and imposed tensile stresses beyond the tensile strength of the cement sheath. (Shadravan et al, 2014;Williams et al, 2011) Pressure increase is more damaging because the fluid injection lasts from minutes to hours (Thiercelin et al, 1998) Several have suggested requirements to tensile strength, Young's modulus, and other mechanical properties of the cement sheath to provide a long-term zonal isolation through long-term stress evaluation (Bois et al, 2011;Bois et al, 2012;Roy-Delage et al, 2000;Saint-Marc et al, 2008;Stiles and Hollies, 2002). Thiercelin et al (1998) analyzed different stress conditions in oil wells which were applicable for most types of loading.…”
Section: Requirements To Cement Systems To Provide Long-term Zonal Ismentioning
confidence: 99%